Orange Peel Derived C‐dots Decorated CuO Nanorods for the Selective Monitoring of Dopamine from Deboned Chicken. Issue 1 (10th October 2019) - Asad, Muhammad; Zulfiqar, Anam; Raza, Rizwan; Yang, Minghui; Hayat, Akhtar; Akhtar, Naeem
Abstract: A novel electrode based on orange peel derived C‐dots decorated CuO nanorods (CR@C‐dot) modified lead pencil (LP) electrode has been fabricated for highly sensitive and selective monitoring of dopamine (DA). Prior to the functionalization with C‐dot, electrochemical efficacy of CR was evaluated and compared with CuO nano‐needles (CN) and nano‐spheres (CS). The morphology, surface area and composition of synthesized nanoparticles was confirmed through field emission scanning electron microscopy (FE‐SEM), N2 ‐adsorption‐desorption isotherm, X‐ray diffraction (XRD), Raman spectroscopy and X‐ray photoelectron spectroscopy (XPS). Our results indicated that CR has high electrocatalytic activity compared to CN and CS by expositing greater fraction of catalytic active sites, large surface area and short diffusion pathways. The electrochemical efficacy of CR is further enhanced by decorating with orange peel derived C‐dots, which surprisingly lead to the integrations of surface‐active sites with current collectors with minimum resistance by acting as an electron transport mediator and providing more surface defects. The developed CR@C‐dot sensor enables highly sensitive and selective recognition of DA detection (0.0007 μM), over good linear range (5–2250 μM) with rapid response time. the developed CR@C‐dot sensor was successfully used to monitor the DA from deboned chicken, thus suggesting reliability of the developed electrode. Abstract :